2002
DOI: 10.1136/bmj.324.7340.768
|View full text |Cite
|
Sign up to set email alerts
|

Randomised controlled trial of short bursts of a potent topical corticosteroid versus prolonged use of a mild preparation for children with mild or moderate atopic eczema

Abstract: Objective To determine whether a three day burst of a potent corticosteroid is more effective than a mild preparation used for seven days in children with mild or moderate atopic eczema. Design Randomised, double blind, parallel group study of 18 weeks' duration. Setting 13 general practices and a teaching hospital in the Nottingham area. Participants 174 children with mild or moderate atopic eczema recruited from general practices and 33 from a hospital outpatient clinic. Interventions 0.1% betamethasone vale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
100
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 144 publications
(101 citation statements)
references
References 17 publications
0
100
0
1
Order By: Relevance
“…Six of the trials 113,[116][117][118]121 had > 100 participants and six 112,114,115,119,120,122 had ≤ 50 participants. The treatment regimens varied, with one trial providing 7 days of treatment as required over an 18-week period 116 one trial providing either twice daily treatment for 8 weeks or twice daily treatment for four consecutive days per week for 8 weeks, 122 and the other trials providing continuous treatment for periods from 2 weeks to 42 days. [112][113][114][115][117][118][119][120] An additional four trials [123][124][125][126] were reported that compared a new active treatment against a topical corticosteroid as the 'standard treatment' comparator.…”
Section: Studiesmentioning
confidence: 99%
See 3 more Smart Citations
“…Six of the trials 113,[116][117][118]121 had > 100 participants and six 112,114,115,119,120,122 had ≤ 50 participants. The treatment regimens varied, with one trial providing 7 days of treatment as required over an 18-week period 116 one trial providing either twice daily treatment for 8 weeks or twice daily treatment for four consecutive days per week for 8 weeks, 122 and the other trials providing continuous treatment for periods from 2 weeks to 42 days. [112][113][114][115][117][118][119][120] An additional four trials [123][124][125][126] were reported that compared a new active treatment against a topical corticosteroid as the 'standard treatment' comparator.…”
Section: Studiesmentioning
confidence: 99%
“…A total of 12 trials [112][113][114][115][116][117][118][119][120][121][122] were reported from 2000 onwards, with two trials reported together in one report. 113 Ten of these trials compared novel topical corticosteroids with standard topical corticosteroids and one trial 118 compared a topical corticosteroid with and without the addition of a penetration-enhancing drug.…”
Section: Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Less potent topical steroids such as hydrocortisone can also be employed to children less than 1 year old. Different therapeutic schemes have been established: initial treatment should be with moderate to high potent steroids followed by a dose reduction or an exchange to a lower potency preparation 75 .…”
Section: ) Anti-inflammatory Therapymentioning
confidence: 99%